1996
DOI: 10.1111/j.1365-2591.1996.tb01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing apical deformation and transportation following the use of LightSpeedTM root‐canal instruments

Abstract: The LightSpeed root canal instrument is similar in design to the Canal Master instrument with the exception of being engine driven and fabricated from nickel-titanium alloy. The purpose of the design of these instruments is to reduce apical transportation of the canal during cleansing and shaping procedures. Twenty extracted human molar teeth with roots of varying degrees of curvature were used in this study. A double exposure radiographic technique was used to assess the presence or absence of apical transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 12 publications
2
34
0
1
Order By: Relevance
“…83 Unlike stainless steel instruments, rotary NiTi files are able to predictably "machine" a canal to accurate dimensions, and are able to safely enlarge even curved root canals to sizes not routinely attainable with steel files. 31,84 In recent times, much emphasis has been placed on the preparation of greater root canal taper. This is largely based on obturation philosophy, whereby rootfilling techniques employing thermoplasticised material advocate a canal preparation with greater taper and minimal apical preparation size (ISO size 20, 25, or 30), thereby permitting compaction of the root filling with less chance of extrusion.…”
Section: Size Of the Apical Preparationmentioning
confidence: 99%
“…83 Unlike stainless steel instruments, rotary NiTi files are able to predictably "machine" a canal to accurate dimensions, and are able to safely enlarge even curved root canals to sizes not routinely attainable with steel files. 31,84 In recent times, much emphasis has been placed on the preparation of greater root canal taper. This is largely based on obturation philosophy, whereby rootfilling techniques employing thermoplasticised material advocate a canal preparation with greater taper and minimal apical preparation size (ISO size 20, 25, or 30), thereby permitting compaction of the root filling with less chance of extrusion.…”
Section: Size Of the Apical Preparationmentioning
confidence: 99%
“…Currently, there are approximately 15 different brands and designs of NiTi rotary endodontic instruments on the market. These NiTi rotary instruments are much more flexible than the older stainless steel hand files (3) and have properties that have helped reduce the incidence of canal transportation, zipping and ledge formation by producing rounded, more centered preparations in a reduced time (4,5). Tan and Messer also demonstrated that the rotary instrument produced a cleaner canal compared to hand files (6).…”
mentioning
confidence: 95%
“…No que diz respeito a limpeza, pelo fato da conicidade ser grande nos 3mm apicais do instrumento, uma boa dilatação é garantida. Fazendo uma relação com a clínica endodôntica, em casos onde se necessita uma maior dilatação como nas necroses, o profissional pode realizá-la de modo manual ou rotatório com limas de menor conicidade e calibres de pontas maiores sem ocorrências de acidentes indesejáveis como desvios da trajetória original do canal radicular 25,26 . Cuidados são exigidos na obtenção dos cortes, pois há possibilidade de perda de material durante o procedimento.…”
Section: Discussionunclassified